Potential and future geographical distribution of Eremanthus erythropappus (DC.) MacLeish: a tree threatened by climate change - Carvalho, Monica Canaan (2019)
Eremanthus erythropappus is a commercially-important tree which has a long history of exploitation in the Brazilian State of Minas Gerais. The knowledge on the potential geographical distribution of E. erythropappus is therefore critical for the species sustainability. Thus, the aim of this study was to estimate and map current and future ecological niche for E. erythropappus in Minas Gerais. We used the Random Forests algorithm to model the ecological niche for current and future climates scenarios. Our predictions indicate Espinhaço, Mantiqueira, and Canastra mountain ranges as core areas of distribution and forecast drastic reductions in potential areas under all climate scenarios. Based on our results, we highlight that the continual harvesting of naturally-occurring E. erythropappus populations will not be sufficient to supply the market demand. Silviculture practices would likely serve as an economically viable and ecological sustainable alternative to harvesting natural populations.